High versus low radioiodine activity in patients with differentiated thyroid cancer: A meta-analysis. (August 2013) - Valachis, Antonis; Nearchou, Andreas
Abstract Background. The purpose of the meta-analysis was to estimate the effectiveness and toxicity of low activity radioiodine ablation versus high activity in patients with differentiated thyroid cancer (DTC). Design. A systematic review and meta-analysis was performed by including all randomized trials of low activity versus high activity radioiodine ablation after thyroidectomy. Standard meta-analytic procedures were used to analyze the study outcomes. Results. Ten trials were considered eligible and were further analyzed. The pooled risk ratio (RR) of having a successful ablation for an activity of 1100 MBq versus 3700 MBq (seven trials, 1772 patients) was 0.94 (95% CI 0.85–1.04, p-value = 0.21). The RR for successful ablation when only thyroid hormone withdrawal was used (five trials, 1116 patients) was 0.87 (95% CI 0.72–1.06, p-value = 0.17) and it was comparable to RR when only recombinant-human TSH (rec-hTSH) (two trials, 812 patients) was used (1.00, 95% CI 0.93–1.07, p-value = 0.92). Salivary dysfunction, nausea, and neck pain were significantly more frequent among patients with higher dose for ablation. Conclusion. Our meta-analysis provides some evidence from randomized trials that a lower activity of radioiodine ablation is as effective as higher dose after surgery in patients with DTC with lower toxicity.